The Effect of Video Education on Skin-to-Skin Contact at the Time of Delivery: A Randomized Controlled Trial - Catherine M. Caponero; Dani G. Zoorob; Victor Heh; Hind N. Moussa (Thieme Medical Publishers, Inc., 2022)
Abstract Objective The objective of this study was to measure the impact of video education at the time of admission for delivery on intent and participation in skin-to-skin contact (SSC) immediately after birth. Methods This study was a randomized controlled trial of educational intervention in women (N = 240) of 18 years or older admitted in anticipation of normal spontaneous term delivery. Alternate patients were randomized into video (N = 120) and no video (N = 120) groups. Both groups received a survey about SSC. The video group watched an educational DVD and completed a postsurvey about SSC. Results During the preintervention survey, 89.2% of those in the video group compared with 83.3% of those in the no video group indicated that they planned to use SSC (p = 0.396). After the video, 98.3% planned to do SSC after delivery (p < 0.001). However, only 59.8% started SSC within 5 minutes of delivery in the video group and only 49.4% started SSC within 5 minutes of delivery in the no video group (p = 0.17). Conclusion Video education alters the intention and trends toward participation in SSC within 5 minutes of delivery. Despite the plans for SSC, however, there was no significant difference in rates between the two groups. These findings support that obstacles, other than prenatal education, may affect early SSC. Key Points Significant obstacles impact skin-to-skin rate. Video education alters skin-to-skin intent. Video education can improve skin-to-skin rate. Education can happen at the time of delivery. Video education can impact mothers and infants.